Do Patient-Reported Outcomes Have a Role in the Management of Patients with Cystic Fibrosis? - Salek, Sam (Frontiers in Pharmacology, 2012)
Background: Health-related quality of life (HRQoL) is a rapidly growing area of expertise and the most commonly used patient-reported outcome (PRO). The impact of CF on HRQoL is liable to be great, making CF patients ideal candidates for the application of HRQoL instruments. The aims of this study were to assess the affect of CF on HRQoL, to ascertain the reliability and validity of the UKSIP and the CFQoL in the adult CF population, and to examine their role in the management of patients. Methods: Seventy participants were recruited from the All Wales Adult Cystic Fibrosis Centre at Llandough Hospital, UK. There were two stages to the study; self-report of the UKSIP and CFQoL in the first stage, and completion of the same two questionnaires seven to ten days later for the second stage. Results: The areas of HRQoL most impaired by CF were employment and concerns regarding the future. The UKSIP and CFQoL showed high internal consistency (rα=0.89-0.93) and test-retest reliability (rs=0.57-0.94, p<0.005) in the CF population. Validity was variable; with the UKSIP showing discrimination across socio-demographic factors, whilst the CFQoL showed increased sensitivity to clinical variables. Many parameters influenced patient-reported HRQoL, with the greatest correlations seen with the Borg score (p<0.005). The use of a HRQoL instrument in CF annual reviews is recommended to provide holistic patient care. The results of this study underpin the value of HRQoL as a patient-reported outcome measure in the management of adult CF.